PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN RECONNECTING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIKIH KELAS VII MTsN 1 LANGKAT - Muamar Al Qadri, Zubaidah Nur Bilqis (Jurnal Iqtirahaat, 2022)
This research is motivated by the existence of symptoms that indicate that the Fiqh teacher has used the Reconnecting strategy well while the students' Fiqh learning outcomes are still not good. This study aims to determine the effect of using the Reconnecting learning strategy on student learning outcomes in Fiqh subjects at Madrasah Tsanawiyah Negeri 1 Langkat. This research was conducted in the even semester of the 2021/2022 academic year. The population of this study was the entire class VII of Madrasag Tsanawiyah Negeri 1 Langkat totaling 225 students. The research sample amounted to 45 students. Sampling using simple random sampling technique. Methods of data collection using questionnaires, tests and documentation. The data analysis technique uses product moment correlation with the help of SPSS statistics 28.0.0.0. The results of the data research analysis showed that there was a significant correlation between the use of the Reconnecting learning strategy and the learning outcomes in Fiqh subjects at Madrasah Tsanawiyah Negeri 1 Langkat. The correlation coefficient value of 0.490 is greater than rtable at the 5% significance level (0.301). Significant value 0.001 < 0.05 then Ha is accepted and Ho is rejected. The contribution of the Reconnecting learning strategy to student learning outcomes in Jurisprudence subjects is 49%.